Therapeutic potential of hydrogen-rich water in zebrafish model of Alzheimer’s disease: targeting oxidative stress, inflammation, and the gut-brain axis - He, Jiaxuan; Xu, Peiye; Xu, Ting; Yu, Haiyang; Wang, Lei; Chen, Rongbing; Zhang, Kun; Yao, Yueliang; Xie, Yanyan; Yang, Qinsi; Wu, Wei; Sun, Da; et al. (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder, with amyloid-beta (Aβ) aggregation playing a key role in its pathogenesis. Aβ-induced oxidative stress leads to neuronal damage, mitochondrial dysfunction, and apoptosis, making antioxidative strategies promising for AD treatment. This study investigates the effects of hydrogen-rich water (HRW) in a zebrafish AD model. Zebrafish were exposed to aluminum chloride to induce AD-like pathology and then treated with HRW using a nanobubble device. Behavioral assays, ELISA, Hematoxylin–eosin (H&E) staining, and reactive oxygen species (ROS) and neutrophil fluorescence labeling were employed to assess HRW’s impact. Additionally, 16S rRNA sequencing analyzed HRW’s effect on gut microbiota. HRW can significantly improve cognitive impairment and depression-like behavior in zebrafish AD model, reduce Aβ deposition (p < 0.0001), regulate liver Soluble epoxide hydrolase (sEH) levels (p < 0.05), reduce neuroinflammation, and reduce oxidative stress. Furthermore, HRW reduced the number of harmful bacteria linked to AD pathology by restoring the balance of microbiota in the gut. These findings suggest that HRW has potential as a therapeutic strategy for AD by targeting oxidative stress, inflammation, and gut-brain axis modulation.